2018
DOI: 10.1155/2018/7923575
|View full text |Cite
|
Sign up to set email alerts
|

Axial Behaviour of Slender RC Circular Columns Strengthened with Circular CFST Jackets

Abstract: is paper investigates the axial behavior of slender reinforced concrete (RC) columns strengthened with concrete filled steel tube (CFST) jacketing technique. It is realized by pouring self-compacting concrete (SCC) into the gap between inner original slender RC columns and outer steel tubes. Nine specimens were prepared and tested to failure under axial compression: a control specimen without strengthening and eight specimens with heights ranging between 1240 and 2140 mm strengthened with CFST jacketing. Exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…e eight-node reduced integration linear solid elements with three translation degrees of freedom (C3D8R) were utilised for modelling the steel tube, corrugated steel plate, concrete and loading plates [1][2][3][4]. Obviously, the thin-walled steel tube used in the ISSCC column buckles locally outwards with the extrusion provided by the filled concrete.…”
Section: Element Type and Sizementioning
confidence: 99%
See 1 more Smart Citation
“…e eight-node reduced integration linear solid elements with three translation degrees of freedom (C3D8R) were utilised for modelling the steel tube, corrugated steel plate, concrete and loading plates [1][2][3][4]. Obviously, the thin-walled steel tube used in the ISSCC column buckles locally outwards with the extrusion provided by the filled concrete.…”
Section: Element Type and Sizementioning
confidence: 99%
“…e CFST column composes of an empty steel tube filled with concrete, at which both materials sustain together the applied axial load. In recent years, CFST column has widely been used in various building structures and bridges due to good mechanical properties and construction performance [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Ren and Chen et al 17,18 analyzed the full range bearing performance and failure characteristics of fully grouted bolts based on the tri-linear bond-slip model of the anchorage interface. Lu and Wang et al [19][20][21] used an improved tri-linear bond-slip model of the anchorage interface to analyze the pullout bearing properties of fully grouted bolts. Jiang and Song et al 22,23 used FLAC3D numerical software to study the pullout bearing characteristics of fully grouted bolts.…”
Section: Introductionmentioning
confidence: 99%
“…However, the studies about CFST jacketing strengthening mostly focus on the RC columns (Li et al, 2019;Lu et al, 2016Lu et al, , 2018. These previous investigations on the behaviour of stub and slender RC columns strengthened by CFST jacketing showed that all retrofitted specimens behaved in a ductile manner with the load-bearing capacity and ductility significantly enhanced.…”
Section: Introductionmentioning
confidence: 99%